'Bent on Candor': gossip, shame, and Capote's Answered Prayers. Issue 4 (6th June 2016) - St. Pierre, Scott
Abstract : This essay argues for a reconsideration of Truman Capote's unfinished final novel Answered Prayers as merely an exercise in trivial gossip. Rather, it argues that Capote's use of gossip in the novel is an effective instance of using affect as queer resistance to the sexually normalising forces that have historically labelled the novel as scarcely more than tabloid trash.